Letter from James Curtis Booth to Daniel M. Fox, October 1, 1885 - Booth, James Curtis (1885)
James Curtis Booth (1810-1888) responds to a report by Daniel M. Fox (1819-1890), Superintendent of the United States Mint at Philadelphia from 1885-1890, asserting that the New Orleans Mint is operating more efficiently than the Mint at Philadelphia.
Keywords: Booth, James Curtis, 1810-1888; Fox, Daniel M. (Daniel Miller), 1819-1890; United States Mint; Mint of the United States